The role of clusters in creating value in supply chains: evidence from the examination of clusters with RBV - Wood, Lincoln (Tilde University Press, 2010)
The role of clusters within larger supply chains has received little attention, yet there is evidence that clustering can bring significant advantages to member firms. This investigation focuses on supply chain management capabilities in clusters through the examination using the Resource Based View (RBV). The strategic implications of clustering and the role that clusters can play in creating value in the supply chain are explicated for one cluster. Capabilities relating to information sharing and willingness to share information, structures for sharing of risks and rewards, market mediation, and return stabilisation, are identified as key methods used by the cluster to generate value and operate successfully.